2015
DOI: 10.1017/s0950268815001521
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing pneumonia due to clonally diverse Staphylococcus aureus strains producing Panton-Valentine leukocidin: the Czech experience

Abstract: A prospective study (2007-2013) was undertaken to investigate clinical features and prognostic factors of necrotizing pneumonia caused by Staphylococcus aureus producing Panton-Valentine leukocidin (PVL) in the Czech Republic. Twelve cases of necrotizing pneumonia were detected in 12 patients (median age 25 years) without severe underlying disease. Eight cases occurred in December and January and the accumulation of cases in the winter months preceding the influenza season was statistically significant (P < 0·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Panton–Valentine leukocidin (PVL), for instance, is a key virulence factor. Previous studies have shown the association between PVL and severe invasive infections 9,10. Thus, it is important to characterize the virulence factors of CA- S. aureus for improving therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Panton–Valentine leukocidin (PVL), for instance, is a key virulence factor. Previous studies have shown the association between PVL and severe invasive infections 9,10. Thus, it is important to characterize the virulence factors of CA- S. aureus for improving therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an isolate belonging to ST30/t318 was reported for the first time in Italian pig farms with this work, although ST30 carrying other spa-types (i.e., t012 and t093) were isolated from swabs collected in slaughterhouses located in Southern Italy (Normanno et al, 2015). Isolates belonging to ST30 have been described as CA-MRSA; in particular, ST30/t318 has been reported to be responsible for abscesses, bloodstream or necrotic infections in different parts of the world (e.g., Czech Republic, China) (Jiang et al, 2013;Rájová et al, 2016), and the presence of an isolate collected from farm belonging to this lineage is of concern for the health of people coming into contact with animals.…”
Section: Discussionmentioning
confidence: 80%
“…Isolates belonging to ST30 have been described as CA-MRSA; in particular, ST30/t318 has been reported to be responsible for abscesses, bloodstream or necrotic infections in different parts of the world ( e.g. , Czech Republic, China) (Jiang et al , 2013 ; Rájová et al , 2016 ), and the presence of an isolate collected from farm belonging to this lineage is of concern for the health of people coming into contact with animals. Finally, the molecular characterization allowed to identify an isolate belonging to a novel ST, further characterized as ST5422, showing spa -type t1730.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus strain NRL 08/001 (=CNCTC 7452), belonging to sequence type 154 (ST154) and spa type t667 (3), was isolated from a fatal case of pneumonia in a 22-year-old patient in 2007 in the Czech Republic (4). Only a few PVL-positive ST154 strains have been reported in western Europe (57) and Japan (8), but wide distribution of this clone was found in Mongolia (9).…”
Section: Announcementmentioning
confidence: 99%